2017
DOI: 10.1002/admt.201700274
|View full text |Cite
|
Sign up to set email alerts
|

Niobium Alloying of Self‐Organized TiO2 Nanotubes as an Anode for Lithium‐Ion Microbatteries

Abstract: Self‐supported titanium dioxide nanotube is explored as a potential negative electrode for 3D Li‐ion (micro) batteries. Apart from the direct contact of the nanotubes with the substrate, the 1D porous structure effectively facilitates the flow of electrolyte into the bulk, alleviates any volume expansion during cycling, and provides a short lithium‐ion diffusion length. The fabrication of self‐supported Nb rich titanium dioxide nanotubes by electrochemical anodization of Ti–Nb alloys is reported. The structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…In both studies, the anatase structure of the doped sample was confirmed via XRD. Furthermore, a significant enlargement of the lattice parameters was determined and found to result from the incorporation of Nb 5+ and displacement of Ti 4+ in the oxide matrix . Average specific capacity values of around 160 mAh g −1 with an overall capacity retention of almost 90% after 100 cycles were found for TiO 2 NTs with a 10 wt% Nb content.…”
Section: Li‐ion Batteries With Anodically Grown Tio2 Nanotube Anodesmentioning
confidence: 95%
See 2 more Smart Citations
“…In both studies, the anatase structure of the doped sample was confirmed via XRD. Furthermore, a significant enlargement of the lattice parameters was determined and found to result from the incorporation of Nb 5+ and displacement of Ti 4+ in the oxide matrix . Average specific capacity values of around 160 mAh g −1 with an overall capacity retention of almost 90% after 100 cycles were found for TiO 2 NTs with a 10 wt% Nb content.…”
Section: Li‐ion Batteries With Anodically Grown Tio2 Nanotube Anodesmentioning
confidence: 95%
“…Average reversible capacity values for different types of anodic self‐organized nanotubes recorded at rates between 0.1 C and 2 C. Data collected from refs. .…”
Section: Li‐ion Batteries With Anodically Grown Tio2 Nanotube Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…A general advantage of all vertically aligned nanotubes grown by anodic oxidation is that they offer a direct electron pathway to a back contact (in contrast to particle‐like nanostructures). Therefore, throughout the past decades, TiO 2 nanotubes, specifically conventional CP TiO 2 nanotubes, have been extensively studied for a wide range of applications where this direct electrode contact is beneficial, such as dye‐sensitized solar cells,, fuel cells,, Li‐ion batteries,, photocatalysts,, bio‐applications, and sensors . As SP NTs have been only recently introduced, relatively little is known about their properties – particularly their photoelectrochemical properties, in comparison to conventional close‐packed tubes.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to the replacement of the TiO 2 NP structure with alternative, TiO 2 nanotubes (NTs) for DSCs offer several advantages due to increased light scattering, fast electron transportation and reduction of trap sites compared to TiO 2 NPs [19,20]. Pristine and chemically modified TiO 2 NTs have been studied as photoelectrodes for DSCs and energy storage systems [21,22]. To the best of our knowledge, the most of publications which deal with TiO 2 NTs-based photoelectrodes report the fabrication of nanotubes by anodization of the Ti foils that is rather a complicated fabrication method [20,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%